The The Implementation of a National Strategic Plan on Strengthening Knowledge of Antimicrobials Resistance and Awareness of Rational Antimicrobial Use among the Public: The Implementation of a National Strategic Plan on Strengthening Knowledge of Antimicrobials Resistance and Awareness of Rational Antimicrobial Use among the Public - Saengungsumalee, Shinnawat; Sirisinsuk, Yupadee; Theeraroungchaisri, Anuchai (RATANABUTH JOURNAL, 2023)
In August 2016, the Council of Ministers of Thailand approved the National Strategic Plan on AMR 2017-2021. One of the strategic plans was strengthening knowledge of antimicrobial resistance (AMR) and awareness of rational antimicrobial use (AMU) among the public. The objectives of this study were to collect the activities implemented to achieve the goal of the fifth strategy by provincial public health offices, hospitals, and the Health Department of the Bangkok Metropolitan Administration. Two survey rounds were conducted from January to March 2022. The first round was for the respondents at PPH and HDBMA, and the second one was for those in hospitals. The questionnaire consisted of closed-ended questions. Descriptive statistics performed data analysis. The survey results from respondents thought knowledge training resulted in the target group having the most knowledge and awareness about AMR and AMU. The respondents used educational brochures and posters to disseminate AMR and AMU knowledge. The target groups for which the respondents organized activities to raise knowledge about AMR and awareness of AMU were public health professionals and patients. The survey how much the activities organized or conducted by the survey respondents focused on content issues in knowledge and awareness most survey respondents emphasized all issues, with an average score of more than 4 out of 5. These findings show a need for suitable activities to promote knowledge of AMR and raise awareness of AMU to target groups.